The Construction of Popular Islamic Media Narratives on The Issues of Sexual Violence in Indonesia - Athik Hidayatul Ummah (DINIKA : Academic Journal of Islamic Studies, 2026)
This study examines the construction of media narratives on sexual violence and analyzes how Islamic popular media in Indonesia articulate this issue in cyberspace. The topic is significant because sexual violence is a global concern and a key target of the Sustainable Development Goals, while media coverage often reproduces gender bias, sexism, and misogynistic framing. Using qualitative content analysis and Walter Fisher’s narrative paradigm, this study analyzes discourse produced by three Islamic popular media outlets: MuslimahNews.net, BincangMuslimah.com, and Mubadalah.id. The findings show that Islamic popular media position themselves as platforms for education, religious literacy, and the prevention of sexual violence by promoting inclusive and gender-equitable narratives. However, narrative constructions differ according to each outlet’s ideological orientation. MuslimahNews.net frames sexual violence as a consequence of secular capitalist systems and proposes the Islamic system as the primary solution. BincangMuslimah.com attributes sexual violence to the erosion of human dignity and value inequality, advocating practical prevention measures, legal responses, and the involvement of religious leaders. Mubadalah.id constructs sexual violence as rooted in patriarchal culture, gender injustice, and biased religious interpretations, emphasizing the deconstruction of such interpretations and the promotion of shared social responsibility. These findings demonstrate that Islamic popular media offer diverse narrative strategies that can function as counter-narratives to gender-biased mainstream media and contribute to more ethical and inclusive public discourse on sexual violence.